The Reduced Preservation of Bajidor Art by Foreign Cultures - Danistiar Arif Putra; Neng Aas Fauziah Rohmah; Tiara Citra Rahayu (The International Journal of Politics and Sociology Research, 2020)
Art, which is one of the elements of universal culture, is an element that can highlight its characteristics, characteristics and mouth, thus art is the most important element in Indonesian national culture. The life and death of Bajidor cannot be separated from dependence on the supporting community, especially the Bajidor community is considered as a form. The art of bajidoran dance that developed is better known as klining-bajidoran and may be influenced by the Bandung area. Many do not know this primitive Indonesian art. Because foreign cultures are more easily accepted by the younger generation. Our research method uses qualitative research methods. With interviews, the data we need will be available to complete the mini research with the title we took. The arrival of foreign cultures to Indonesia often enters without filtering those consuming foreign cultures. Foreign cultures that come are also often glorified by the Indonesian people. These things are factors that cause "the lack of preservation of bajidoran arts by foreign cultures". Bajidor art itself in fact has a uniqueness that is not owned by art from abroad. More than that, bajidor art can also be used in various celebration events.